PENGARUH PELAYANAN DAN EKSPERIENTIAL MARKETING TERHADAP KEPUASAN ANGGOTA PEMBIAYAAN BMT BEN SEJAHTERA KABUPATEN CILACAP - Anggit Nandya Ratri; Handoyo Djoko W (Jurnal Ilmu Administrasi Bisnis, 2017)
Competition in the business world to force the perpetrators of cooperatives and UKM to have a strategy to win the competition. Financial institutions incorporated in the cooperative now has a lot to facilitate the community in the form of savings and loans and BMT Ben Sejahtera is one of the financial institutions. BMT Ben Sejahtera decreased the percentage of growth in recent years and the numbers are fairly high dissatisfaction.This research aimed to determine the effect of service (X1) and experiential marketing strategy (X2) the satisfaction (Y) member financing at KJKS BMT Ben Sejahtera Cilacap. This type of research is explanatory research with data collection through questionnaires and interviews. The population in this research are members who have committed financing in BMT Ben Sejahtera some 2,062 members. The sample in this study amounted to 96 people who obtained using the technique of non-Probability Sampling with purpusove sampling techniques.The quantitative analysis in this study using cross table test, correlation, coefficient of determination, simple and multiple regression, significance test (t test) in one tail and Annova test (F test). The results show the positive influence between services and experiential marketing to the satisfaction of either partially or simultaneously. This means that when services are rendered and experiential marketing (lessons learned), the better, the higher the satisfaction derived by the members.Suggestions for the company is to create a better service to members, especially in the indicators of empathy, but it also required an increase in the creation of experiential marketing (marketing based on experience). This is realized in the framework of the creation of member satisfaction.